Health-related quality of life in systemic sclerosis before and after autologous haematopoietic stem cell transplant—a systematic review. (27th August 2019) - Puyade, Mathieu; Maltez, Nancy; Lansiaux, Pauline; Pugnet, Grégory; Roblot, Pascal; Colmegna, Ines; Hudson, Marie; Farge, Dominique
Abstract: Objectives: In severe rapidly progressive SSc, autologous haematopoietic stem cell transplantation (AHSCT) allows significant improvements in overall and event-free survival. We undertook this study to identify, appraise and synthesize the evidence on health-related quality of life (HRQoL) before and after AHSCT for SSc. Methods: We performed a systematic review of the literature, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, in PubMed and ScienceDirect from database inception to 1 February 2019. All articles with original HRQoL data were selected. Results: The search identified 1080 articles, of which 8 were selected: 3 unblinded randomized controlled trials [American Scleroderma Stem Cell versus Immune Suppression Trial (ASSIST), Autologous Stem Cell Transplantation International Scleroderma, Scleroderma: Cyclophosphamide or Transplantation), 3 uncontrolled phase I or II trials and 2 cohort studies. HRQoL data from 289 SSc patients treated with AHSCT and 125 treated with intravenous CYC as a comparator with median 1.25–4.5 years follow-up were included. HRQoL was evaluated with the HAQ Disability Index (HAQ-DI; 275 patients), the 36-item Short Form Health Survey (SF-36; 249 patients) and the European Quality of Life 5-Dimensions questionnaire (EQ-5D; 138 patients). The quality of the studies was moderate to low. AHSCT was associated with significant improvement in the HAQ-DI ( P = 0.02–<0.001), SF-36 Physical Component Summary score ( P = 0.02–<0.0001) and EQ-5D index-based utility score ( P < 0.001). The SF-36 Mental Component Summary score improved in the ASSIST ( n = 19) and one small retrospective cohort ( n = 30 patients, P = 0.005) but did not improve significantly in 2 randomized controlled trials ( n = 200 patients, P = 0.1–0.91). Conclusion: AHSCT in severe SSc patients is associated with significant and durable improvement in physical HRQoL.